Strategic Effort for Tourism Guide Tourism Development in Besakih Village Area Post-Covid-19 Pandemic - AAA. Ngr. Sri Rahayu Gorda; Ketut Elly Sutrisnis; Ida Ayu Oka Martini (Fakultas Hukum, Universitas Warmadewa, 2022)
Efforts are made to the development of sectors of the economy, business, and tourism in promoting the needed strategy which aims to determine the effectiveness of the campaign that carried the Department of Tourism Village Besakih in improving return the number of visits wisatawannya to the village of Besakih post pandemic Covid 19 In this method of community service activities, namely using the method of observation, interviews, and documentation. Based on the results of the study the data in the above can be concluded that the strategy of promotion of the Office of Tourism and the village of Besakih in increasing the number of travelers per week experienced peningkatan.hal it can be seen from the data visit travel Desa Besakih on the chart above.